Nehru and the people's movement - Sharma, Jagdish P.; Patnaik, Saroj K.; Mohanty, Debadatta (New Delhi : Manak Publications, 1997)
Collection of papers presented at a seminar organized by academicians.
Includes bibliographical references.
Keywords: Nehru, Jawaharlal, -- 1889-1964 -- Political and social views -- Congresses